The role of Kyai in developing Islamic social entrepreneurship as an effort to achieve SDGs in Islamic boarding schools - Hafidloh, Hafidloh; ramadania, Ramadania; rosnani, Titik (International Journal Labs, 2025)
Kyai is a leader in an Islamic boarding school institution who has a central role as a founder, driver of change, and decision-maker. Kyai is the key to integrating Islamic values ??into a sustainable business model that aims not only for profit but also for non-profit. Therefore, The purpose of this study is to understand the role of kyai in optimizing the social function of Islamic boarding school business units, the problems faced in developing social entrepreneurship, and the steps to solve them. This study used a qualitative approach with an ethnographic case study design. This approach was chosen to deeply understand the phenomenon of the role of leadership in Islamic Social Entrepreneurship (ISE) in two Islamic boarding schools, namely PABS and PPSD. As a framework for exploring values ??and culture in two Islamic boarding schools, it had similarities but was different in the development of ISE. The results of this study indicated that the role of kyai as the founder and main driver, strategic policy maker, inspirator, and innovator. Using each leadership style approach conditionally. Visionary, transformational, servant, participatory, and bottom-up (organizationally) were the leadership styles of kyai PPSD, while visionary, autocratic, servant, participatory, and top-down were the leadership styles of kyai PABS. Both Islamic boarding schools implemented different strategies that were adjusted to the geographical, demographic, and cultural contexts. PABS, for example, focused on digitalization adaptation, HR development through training, and regeneration. PPSD implemented a Good Corporate Governance (GCG) strategy by utilizing sky marketing and business unit diversification.